Modelos pedagógicos que se trabajan en el nivel inicial dos de la escuela Rosario de Alcázar. - Guacho Criollo, Erika Silvana (2018)
The present work constitutes a descriptive study of the pedagogical models in the initial education, of the Rosario de Alcázar School of the Initial Level Two. The main problem that gave rise to the approach of the research is that "a pedagogical model for initial education has not been consolidated", which promotes integral development and a specific education for this level. The general objective for the research carried out was: Know the pedagogical models that are applied in the Initial Level Two of the Rosario de Alcázar School located in the Parish of Conocoto, Province of Pichincha. For the present investigation, the methodology of qualitative type was used, which allowed to collect data, in the group of children of Initial Level Two. To obtain the data, three instruments were designed: the interview with the school principal, the surveys of the teachers at the initial level and the field diaries of each class that was observed. Finally, it was concluded that in the Initial Level Two of the Rosario de Alcázar School it uses the constructivist pedagogical model and the method of María Montessori, starting from the previous knowledge of the children so that they can build their own knowledge from their experiences, through the game methodology -work where the skills and abilities of each student are developed with the manipulation of toys and didactic materials.